2021
DOI: 10.1177/17474930211007288
|View full text |Cite
|
Sign up to set email alerts
|

International stroke genetics consortium recommendations for studies of genetics of stroke outcome and recovery

Abstract: Numerous biological mechanisms contribute to outcome after stroke, including brain injury, inflammation, and repair mechanisms. Clinical genetic studies have the potential to discover biological mechanisms affecting stroke recovery in humans and identify intervention targets. Large sample sizes are needed to detect commonly occurring genetic variations related to stroke brain injury and recovery. However, this usually requires combining data from multiple studies where consistent terminology, methodology, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…We here only assessed rather coarse-grained behavioral outcomes – with the additional limitation that the NIHS Scale is known to result in higher scores for left-hemispheric lesions. 39 Future studies could therefore specify the impact of WMH and stroke lesion interaction effects on language outcomes or individual NIHSS items as a first step, 40 corroborate the detrimental effects and estimate their clinical relevance further. Conceivably, a more consistent consideration of the WMH burden in models of language-related outcomes may substantially increase the prediction performance.…”
Section: Discussionmentioning
confidence: 99%
“…We here only assessed rather coarse-grained behavioral outcomes – with the additional limitation that the NIHS Scale is known to result in higher scores for left-hemispheric lesions. 39 Future studies could therefore specify the impact of WMH and stroke lesion interaction effects on language outcomes or individual NIHSS items as a first step, 40 corroborate the detrimental effects and estimate their clinical relevance further. Conceivably, a more consistent consideration of the WMH burden in models of language-related outcomes may substantially increase the prediction performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider both stroke outcome which describes the degree of function at specific time points; and stroke recovery which comprises the degree of improvement (or deterioration) over time and may better identify dynamic biological processes. 10 We highlight the importance of dynamic phenotypes that may capture mechanisms involved in the injury-repair timeline following stroke. We discuss how genetic studies, including GWASs, can exploit these phenotypes to uncover genes and pathways that shape stroke outcome, from early brain injury to long-term recovery.…”
Section: Lee Et Almentioning
confidence: 99%
“…But there is a risk that the phenotyping is not harmonized between the studies and may also be of insufficient detail to perform studies of quantitative endophenotypes. 10 GWAS can be used to study copy number variations, and one study reported that genetic imbalance is related to poor 3-month outcome after stroke. 59 Other genetic approaches, such as whole-exome sequencing or whole-genome sequencing, are promising, but the implementation due to high costs is still limited.…”
Section: Using Genetics To Explore Mechanisms Underlying Stroke Outcomementioning
confidence: 99%
“…Such studies require data from thousands of cases, and data collection and outcomes need to be standardized across these different cohorts. 3 An useful framework for design of these studies is presented in a consensus paper from the International Stroke Genetics Consortium in this issue. It makes an important reading for anyone planning to carry out studies in this area.…”
mentioning
confidence: 99%
“…It makes an important reading for anyone planning to carry out studies in this area. 3 A potentially exciting novel treatment approach is environmental enrichment. This has been shown to improve recovery in animal models of stroke, promoting brain plasticity and enhancing sensory motor recovery with the greatest gains made when used in conjunction with motor retraining.…”
mentioning
confidence: 99%